The dynamic network characteristics of physical, psychological, and cognitive symptoms of people with HIV based on cross-lagged network analysis in China - Meilian Xie; Xiaoyu Liu; Zhiyun Zhang; Yanping Yu; Li Zhang; Jieli Zhang; Dongxia Wu (PLoS ONE, 2026)
Introduction This study aims to construct a dynamic network by collecting longitudinal data, which will assist medical professionals in identifying bridging symptoms associated with disease progression and causal mechanisms. Methods A longitudinal observational study was conducted from March to June 2024, recruiting an initial cohort of people with HIV (PWH) from three designated AIDS medical institutions in Beijing, China. Symptom data were collected at two time points, three months apart, using the Chinese version of the Self-Report Symptom Scale (SRSS) alongside a demographic questionnaire. The data were analyzed using cross-lagged panel network analysis to explore symptom dynamics over time. Results A total of 791 PWH were recruited and 706 participants (89.25%) continued to the 3-month follow-up, with a mean age of 38.37 ± 10.03 years. There were no significant differences in demographic variables between those who missed and those who completed the study, except for clinical indices such as CD4 + cell count, ART duration, and comorbidity. Psychological symptoms, such as feeling helpless, feeling uneasy, and feeling fearful, also appear frequently. The most significant association identified was between becoming confusing and having difficulty in reasoning (COGS5 → COGS4, OR = 1.20). Notable bridging symptoms across two distinct domains included becoming confusing, leading to hardly focusing on anything (COGS5 → PSYS2, OR = 1.12), feeling hopeless, leading to rash (PSYS8 → PHYS8, OR = 1.11), and worry overwhelming leading to sleep disturbance (PSYS3 → PHYS6, OR = 1.11), among others. Conclusions There is an urgent need to enhance the assessment and early monitoring of cognitive status for PWH.